A revision of Leydigia Kurz, 1875 (Anomopoda, Cladocera, Branchiopoda), and subgeneric differentiation within the genus - Kotov, Alexey A. (Zootaxa, 2009)
A revision of the genus Leydigia Kurz, 1875 (Anomopoda, Cladocera, Branchiopoda) is presented. The list of all species-group nominal taxa consists of 34 published and 3 unpublished names. Of these, 12 species are accepted as valid: (1) Leydigia (Leydigia) leydigi (Schödler, 1863); (2) L. (L.) louisi Jenkin, 1934 with two subspecies L. louisi louisi Jenkin, 1934 and L. louisi mexicana Kotov, Elías-Gutiérrez et Nieto, 2003; (3) Leydigia (Neoleydigia) propinqua Sars, 1903; (4) L. (N.) australis Sars, 1885; (5) L. (N.) microps Sars, 1916; (6) L. (N.) sp. nov. from 'L. acanthocercoides' in Alonso, 1996; (7) L. (N.). macrodonta Sars, 1916; (8) L. (N.) acanthocercoides (Fischer, 1854); (9) L. (N.). laevis Gurney, 1927; (10) L. (N.) cf. ipojucae Brehm, 1939; (11) L. (N.) ciliata Gauthier, 1939; (12) L. (N.) cf. striata Birabén, 1939. Lectotypes are selected for 3, 5, 7, and 9. Exact identification of 10 and 12 is not possible without examination of material from type localities and neotype selection. As confirmed by examination of authors' type material, some taxa (Leydigia africana Gurney, 1904 and Leydigia ankammaraoi Prasad, Santa Kumari et Bose, 1985) prove to be junior synonyms of previously described species; species 8-12 form a compact acanthocercoides-group, with fine differences among members. A cladistic analysis for 13 studied taxa and 18 morphological characters resulted in four most-parsimonious trees (TL = 32; CI = 0.78), which differ only in the grouping of members of the L. acanthocercoides-group. A slightly polytomic strict consensus tree (the 50% majority rule bootstrap simulation led to a tree of similar topology to the contree), as well as some 'orthodox' ideas on the evolution of the genus (not contradicting each other), are used to subdivide the genus into two subgenera, Leydigia (Leydigia) Kurz, 1875 and Leydigia (Neoleydigia) subgen. nov. L. (N.) acanthocercoides is the type species of the latter. A key for the identification of well-known species of Leydigia is provided. The level of description of representatives of the genus Leydigia in different continents is estimated, and perspectives for further investigations are outlined.